Resumption of professional football during the COVID-19 pandemic. Study findings from Iran - Hassanmirzaei, B.; Haratian, Z.; Ahmadzadeh Amiri, A.; Alinejad, M.; Singh, G. (German Journal of Exercise and Sport Research, 2022)
Due to concerns of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) transmission, professional football (soccer) was terminated almost everywhere in the world in early 2020. These are the results from a prospective cohort study conducted in Iran to analyze the resumption of professional football during the coronavirus disease 2019 (COVID-19) pandemic under assigned protocols and regulations. Sixteen teams consisting of 805 individuals formally agreed to follow the rules assigned by the ministry of health and CORONA headquarters in sport, and were subject to study monitoring. The resumption process was implemented over a 5-month period, beginning with a training phase followed by 14 match weeks of professional football. A self-declaration form was provided for the subjects to report any suspicious symptoms immediately and serial PCR testing was performed every 10 days using nasal swab samples. Those with positive tests were to be isolated until the symptoms were resolved or a negative test was returned. Of the 805 individuals included, 17.89% subjects were infected by the SARS-CoV-2 virus (85 players and 59 staff members and officials). Only two matches were canceled in accordance with the regulations, and no severe cases were found. Case-tracing suggested that most transmissions occurred off the pitch. In conclusion, applying strict hygiene protocols and early case identification by performing repetitive PCR testing could benefit the resumption of professional football competitions.